PENGARUH KETERSEDIAAN PRODUK, KUALITAS LAYANAN, DAN KESESUAIAN HARGA TERHADAP KEPUASAN PELANGGAN TOKO PERLENGKAPAN SEKOLAH "FUNKY SOCK" DI KABUPATEN GROBOGAN - Ana Munadhilah; sri martono (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2026)
Background & Purpose: Competition in the retail business of school supplies has become increasingly intense, requiring store managers to maintain product availability, provide high-quality services, and set prices that align with customer expectations. The “Funky Sock” Store in Grobogan has encountered challenges such as limited stock and delays in restocking, which have led to customer dissatisfaction and a potential decline in loyalty. Previous studies on product availability, service quality, and price suitability have produced inconsistent findings, creating a research gap. Therefore, this study seeks to examine the influence of product availability, service quality, and price suitability on customer satisfaction at the “Funky Sock” Store. Method: This study employed a quantitative method. The research population consisted of customers of the Funky Sock Store in Grobogan. A simple random sampling technique was used to select 90 respondents who met the established research criteria. Data were collected using a structured questionnaire with a 5-point Likert scale. The independent variables included product availability (X1), service quality (X2), and price suitability (X3), while the dependent variable was customer satisfaction (Y). Each variable was measured using several indicators adapted from previous studies, and the collected data were analyzed using SPSS version 24. Results: The findings reveal that product availability has a positive and significant impact on customer satisfaction. Service quality also demonstrates a positive and significant effect on customer satisfaction. Furthermore, price suitability contributes positively and significantly to customer satisfaction. Therefore, these three factors are essential elements that shape customer satisfaction levels in the retail industry. Conclusion & Suggestion : This study concludes that maintaining sufficient product stock, enhancing service quality, and applying fair pricing are crucial strategies for improving customer satisfaction. In the case of the “Funky Sock” Store, these three aspects were found to significantly influence customer satisfaction and serve as key factors in sustaining business performance amid intense retail competition. Based on the findings, it is recommended that the “Funky Sock” Store maintain consistent product availability to avoid customer dissatisfaction, while also improving service quality through friendly and responsive interactions. Moreover, pricing should remain aligned with customer purchasing power to foster loyalty. By implementing these strategies, the store is expected to strengthen its competitiveness and continuously enhance customer satisfaction.   Keywords: Product Availability, Service Quality, Price Suitability, Customer Satisfaction